Subtitling strategies in audiovisual translation: A case study of Cultural-Specific Items in Ngeri-Ngeri Sedap - Alfi Rianis Tsani; Esti Junining; Sugeng Hariyanto (English Learning Innovation, 2026)
Audiovisual translation (AVT) plays a crucial role in addressing the challenges of translating Cultural-Specific Items (CSIs) within film subtitles. This study, therefore, aims to analyse the translation procedures employed to render CSIs in the Indonesian film Ngeri-Ngeri Sedap. Using a qualitative descriptive approach, 150 CSIs were extracted from the film’s Indonesian-English subtitles. Each item was analysed using Vinay and Darbelnet’s (1995) classification of translation procedures and evaluated through Pedersen’s (2017) FAR model to assess subtitle quality in terms of functional equivalence, acceptability, and readability. The results show that seven procedures were applied: equivalence, borrowing, transposition, adaptation, calque, modulation, and literal translation. Equivalence was the most dominant strategy, reflecting the subtitler’s effort to convey culturally embedded meanings in a manner that remains accessible to global audiences. Borrowing frequently occurred when referring to Batak culture-specific expressions that had no direct English equivalents, helping to preserve authenticity despite potential reductions in acceptability. Transposition and adaptation supported grammatical clarity and functional meaning, while calque, modulation, and literal translation appeared infrequently due to their tendency to affect naturalness and readability. The study offers practical insights into how translation procedures affect subtitle quality and highlights the importance of culturally informed decision-making in AVT. The results contribute to a deeper understanding of subtitling strategies in Indonesian regional cinema and provide a foundation for further research on cultural mediation in multilingual audiovisual contexts.